Implementasi Rendam Kaki Air Hangat terhadap Penurunan Nyeri Ankle pada Penderita Rheumatoid Arthritis di RS TK II Putri Hijau Medan - Mhd. Fauzul Hakim Lubis; Kipa Jundapri; Suharto Suharto (Jurnal Riset Hesti Medan, 2025)
Rheumatoid arthritis is a chronic autoimmune disease characterized by joint inflammation, pain, stiffness, and decreased mobility. Ankle pain is one of the common complaints that significantly affects patients' daily activities and quality of life. Non-pharmacological interventions such as warm water foot soaking therapy are considered effective in reducing pain through vasodilation and muscle relaxation mechanisms. This study aimed to determine the effectiveness of warm water foot soaking in reducing ankle pain in patients with rheumatoid arthritis. This research employed a descriptive case study design involving two patients at RS TK II Putri Hijau Medan. The intervention was conducted for three consecutive days using warm water with a temperature of 31–37°C for 15–20 minutes. Pain intensity was measured using the Numeric Rating Scale (NRS). The results showed a significant decrease in pain intensity from a scale of 5 (moderate pain) to 2 (mild pain) in both patients after the intervention. Patients also reported increased comfort and improved mobility. In conclusion, warm water foot soaking is effective as a non-pharmacological nursing intervention to reduce ankle pain in patients with rheumatoid arthritis. This therapy is simple, safe, cost-effective, and can be applied independently by patients.